Investigation of secondary findings extracted from comprehensive genome profiling tests: a single-center retrospective observational study - Sugisita, Yodo; Motoyoshi, Ai; Migita, Osuke; Kuga, Asami; Tsugawa, Koichiro; Suzuki, Yuki (Journal of Hereditary Tumors, 2022)
In recent years, advances in personalized cancer care and the widespread use of next-generation sequencing have facilitated comprehensive genome profiling (CGP) for patients with advanced solid tumors. Secondary findings (SFs) of CGP include the determination of a certain frequency of important germline variants, such as genes responsible for hereditary tumors, which can be used for cancer risk prediction and patient and family surveillance. This information is essential to predict personal and/or familial hereditary cancer risk, and should be appropriately linked to surveillance and treatments. In this report, we examined how SFs from CGP are detected and disclosed at our hospital and the status of visits to the Genetics Outpatient Clinic.